The Efficacy of Activated Carbon From Organic Waste in Treating Wastewater Effluent - Japri, Dzikri; Kasmuri, Norhafezah; Zaini, Nurfadhilah; Abdul Hamid, Khuriah; Satoto Endar Nayono; Mojiri, Amin (International Journal of Sustainable Construction Engineering and Technology, 2024)
Increasing population growth with high socio-economic development has changed the world landscape. Due to that, these advancements have resulted in significant challenges, such as water quality degradation and inadequate management of solid waste. Moreover, the overall environmental impacts have threatened water security and caused global warming. In addressing these critical issues, a robust water treatment technology is required. Using activated carbon (AC) to enhance wastewater effluent quality has proven to be a promising and sustainable solution, particularly in developing countries like Malaysia. AC from sugarcane bagasse (SCB), empty fruit bunch (EFB), and rice husk (RH) have been identified as abundant bioresources in Malaysia. These materials possess unique compositions and potential for reuse. The production of AC involves both physical activation through a carbonization process at 600°C and chemical activation through impregnation with ZnCl2. In the study, samples from wastewater effluent were collected and analyzed for several parameters, including total suspended solids (TSS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), ammonia-nitrogen, nitrite-nitrogen, and nitrate-nitrogen. The samples have undergone treatment using activated carbon with various ratios. Here, the removal efficiency of pollutants was determined before and after the batch experiment. It can be denoted that AC, composed of SCB:EFB:RH in a ratio of 1.5:1:1, demonstrated an outstanding performance with an average percentage removal of 97%. Later, a detailed analysis of the physicochemical characteristics of the AC was conducted. The output revealed significant surface modifications and alterations in the functional groups of the AC due to the adsorption process. These findings set a remarkable implication for tertiary treatment in enhancing the quality of effluent. This innovation provides valuable insight into implementing sustainable practices in wastewater treatment operations. Thus, this project holds immense potential by offering cost-effective, environmentally friendly, and adaptation of green technology for long-term solutions.